Kriegstagebuch einer jungen Nationalsozialistin. Die Aufzeichnungen Wolfhilde von Königs 1939-1946 - Keller, Sven 1976- (Schriftenreihe der Vierteljahrshefte für Zeitgeschichte, 2015)
This book documents 6 years of war, the destruction of her home city of Munich, her worries about her father and brother, the defeat and the first post-war months. It offers an authentic view of the war experiences of an adolescent and young woman who regarded herself as a committed National Socialist, and whose self-perception, thinking, and daily life were shaped by membership in the female branch of the Hitler Youth, the Bund Deutscher Mädel